Education management strategies and equity: the case of the program ‘literacy at the right age’ (mais PAIC) - Cruz, Maria do Carmo Meirelles Toledo; Farah, Marta Ferreira Santos; Ribeiro, Vanda Mendes (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2020)
The aim of the current article is to present the management strategies of the ‘Literacy at the Right Age’ Program (Paic - Programa Alfabetização na Idade Certa). This educational policy was implemented in Ceará State in 2007; according to different studies, it helped increasing educational equity. Data collection methodology was based on bibliographic references and on interviews conducted with managers of the State Educational Secretariat and with teachers who worked in the City of Fortaleza. The main management strategies adopted in 13 years of Program lied on reorganizing the Secretariat by creating a department focused on enabling its cooperation with different municipalities; on adopting axes capable of organizing Paic’s action in cascade, starting from the Secretariat until reaching schools; on adopting instruments and tools to enable implementing agents to focus on common goals; on implementing systemic actions; on following-up and monitoring actions and results, with subsequent progress disclosure; as well as on mobilizing municipalities and several social actors.